Artificial intelligence in medicine: 5th Conference on Artificial Intelligence in Medicine Europe, AIME '95, Pavia, Italy, June 25 - 28, 1995 ; proceedings - Barahona, Pedro (Lecture notes in computer science, 1995)
A component-based architecture for automation of protocol-directed therapy -- Coordinating taxonomies: Key to re-usable concept representations -- Generating personalised patient information using the medical record -- Analysis of medical jargon: The RECIT system -- Medical knowledge representation for medical report analysis -- Modelling medical concepts as time-objects -- Modeling medical reasoning with the Event Calculus: an application to the management of mechanical ventilation -- A general framework for building patient monitoring systems -- Semi-qualitative models and simulation for biomedical applications -- Generating explanations of pathophysiological system behaviors from qualitative simulation of compartmental models -- An information-based bayesian approach to history taking -- Medical decision making using Ignorant Influence Diagrams -- Dynamic propagation in causal probabilistic networks with instantiated variables -- Alerts as starting point for hospital infection surveillance and control -- Cooperative software agents for patient management -- High level control strategies for diabetes therapy -- Therapy planning using qualitative trend descriptions -- Adaptation and abstraction in a case-based antibiotics therapy adviser -- Field evaluations of a knowledge-based system for peripheral blood interpretation -- Functional evaluation of SETH: An expert system in clinical toxicology -- Evaluating a neural network decision-support tool for the diagnosis of breast cancer -- Knowledge-based systems for lymph node pathology: A comparison of two approaches -- Mapping laboratory medicine onto the select and test model to facilitate knowledge-based report generation in laboratory medicine -- Machine learning techniques applied to the diagnosis of acute abdominal pain -- Reflections on building medical decision support systems and corresponding implementation in diagnostics shell D3 -- Decision models for cost-effectiveness analysis: a means for knowledge sharing and quality control in health care multidisciplinary tasks -- Model-based application: The Galen structured clinical user interface -- A knowledge-based modelling of hospital information systems components -- Use of a conceptual semi-automatic ICD-9 encoding system in an hospital environment -- Quality assurance and increased efficiency in medical projects with neural networks by using a structured development method for feedforward neural networks (SENN) -- A prototype neural network decision-support tool for the early diagnosis of acute myocardial infarction -- Integration of neural networks and rule based systems in the interpretation of liver biopsy images -- A cooperative and adaptive approach to medical image segmentation -- COBRA: Integration of knowledge-bases with case-databases in the domain of congenital malformation -- Case-based medical multi-expertise: an example in psychiatry -- TIME-NESIS: A data model in managing time granularity of natural-language clinical information -- Induction of expert system rules from databases based on rough set theory and resampling methods -- Sequential knowledge acquisition: Combining models and cases -- Medical fuzzy expert systems and reasoning about beliefs -- Diagnosis of human acid-base balance states via combined pattern recognition for Markov chains -- Intelligence formation problems in children at an early age applying new computer technologies under conditions of rehabilitation center -- Telecardiology -- Modelling a sharable medical concept system: Ontological foundation in GALEN -- A graph-based approach to the structural analysis of proliferative breast lesions. -- A workstation for clinical decision support in a local area network for cardiology -- Knowledge-based education tool to improve quality in diabetes care -- NEPHARM: A pharmacokinetic database for adjusting drug dosage to impaired renal function -- A hybrid architecture for knowledge-based systems -- Representing medical context using rule-based object-oriented programming techniques -- Integration of Neural Networks and knowledge-based systems in medicine -- Generated critic in the knowledge based neurology trainer -- An approach to analysis of qualitative data with insufficient number of quantization levels -- Inductively learned rule for breast cancer domain with improved interobserver reproducibility -- Development and evaluation of a knowledge-based system to support ventilator therapy management -- A neural support to the prognostic evaluation of Cardiac Surgery -- DECISion-support system for radiological diagnostic -- A preliminary investigation into the analysis of electromyographic activity using a system of multiple neural networks -- Knowledge-based system to predict the effect of pregnancy on progression of diabetic retinopathy -- A software to evaluate multislices radiotherapic treatment planning -- TKR-tool: An expert system for Total Knee Replacement management.
Literaturangaben
Keywords: Konferenzschrift -- 1995 -- Pavia; Künstliche Intelligenz; Medizin